Mali : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper and Statistical Annex presents an overview of economic developments in Mali in 1994-95. Despite the impact of the devaluation on government spending, the overall fiscal deficit was limited to 13.7 percent of GDP in 1994, with government revenue declining by the equivalent of 1\2 percentage point of GDP and total expenditure rising by about 3 1\2 percentage points. In 1995, the fiscal situation improved significantly as the overall government deficit, on a commitment basis and excluding grants, was reduced by more than 2 percentage points of GDP.